The Effect of Hammermill Screen Hole Diameter and Hammer Tip Speed on Particle Size and Flowability of Ground Corn - M. Saensukjaroenphon; C. E. Evans; K. H. Sheldon; C. K. Jones; C. B. Paulk; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2017)
A variable frequency drive can be installed on the motor of a hammermill to adjust motor speed and ultimately hammer tip speed. This enables particle size adjustments to be made externally without requiring screens to be changed, therefore reducing idle time. The objective of this study was to determine the effect of screen hole diameter and tip speed on geometric mean diameter (dgw), geometric standard deviation (Sgw), and angle of repose (AoR). Treatments were arranged as a 3 × 3 factorial in a completely randomized design using three screen hole diameters and three hammer tip speeds. Each treatment replicate (n = 3) was manufactured as a separate grinding queue with individual queue samples as the experimental unit. Whole corn was ground using three common screen hole diameter (6/64, 10/64, and 16/64 in.) at varying hammer tip speeds (10,250, 15,375, and 20,500 ft/min). Results indicated a marginally significant linear interaction (P<0.077) between screen hole diameter and tip speed for dgw, and Sgw. For dgw, when tip speed increased from 10,250 to 20,500 ft/min the rate of decrease in dgwwas greater as screen hole diameter increased from 6/64 to 16/64 in. Therefore, when tip speed was increased from 10,250 to 20,500 ft/min, dgwwas reduced by 233, 258, and 305 μm for corn ground using the 6/64, 10/64, and 16/64 in. screen hole diameter, respectively. For Sgw, when tip speed increased from 10,250 to 20,500 ft/min the rate of decrease in Sgwwas smaller as screen hole diameter increased. Therefore, when tip speed increased from 10,250 to 20,500 ft/min, Sgwwas reduced by 0.31, 0.24, and 0.13 for corn ground using the 6/64, 10/64, and 16/64 in. screen hole diameter, respectively. There was no observed interaction between screen hole diameter and tip speed on AoR. Increasing hammer tip speed increased (linear, P<0.001) AoR. Increasing screen hole diameter decreased (linear, P<0.001) AoR. In summary, the particle size range for a specified hammermill screen size can be adjusted through manipulation of the hammer tip speed, which is made possible using motor variable frequency drives. This enables operators to quickly change the particle size output, while reducing idle time in the mill.
Keywords: particle size; hammermill; tip speed